Building EFL Preservice Teachers' Professional Identity: Does Gender Matter? - Elisa Pérez-Gracia; Rocío Serrano-Rodríguez; Alfonso Pontes-Pedrajas (Universidad Nacional de Colombia, 2022)
This study explores the beliefs of English as a foreign language preservice secondary education teachers regarding the construction of teachers' professional identity. A questionnaire was used to obtain the opinions of 131 future teachers in the 2014-2020 academic years. Results showed that the participants understood teachers' professional identity to be connected to the ability to motivate students, manage the classroom, and care about interpersonal relations. Women and men think differently regarding the effect of the acquisition of new methodologies, the psycho-pedagogical training, and a longer placement period in the construction of teachers' professional identity. To conclude, this study provided the chance to reflect on the importance of strengthening the professional identity of English as a foreign language teachers while considering the gender perspective to introduce changes in the curriculum.